Podróż nieoswojona .......... 293 - Banaszkiewicz, Magdalena; Golemo, Karolina; Duda, Anna; Czech, Franciszek; Banaś, Monika (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
AN UNTAMED JOURNEYThe essay offers a critical analysis of contemporary travel, delving into the multifaceted nature of modern travel experiences. The author examines various examples and statistical data to present a nuanced depiction of the current travel landscape. Situated within the frameworks of sustainability and mindfulness, the essay explores how individual experience serves as microcosm of broader global trends, shedding light on their interplay and significance in shaping contemporary travel behaviour.